2016
DOI: 10.1016/j.jjcc.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless aortic valve replacement may improve early mortality compared with transcatheter aortic valve implantation: A meta-analysis of comparative studies

Abstract: Compared with TAVI, sutureless AVR may be associated with a reduction in early mortality and postoperative paravalvular AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
(56 reference statements)
8
13
0
Order By: Relevance
“…However, when a comparison with conventional AVR was made, outcomes were burdened by similar mortality but a reduced rate of permanent pacemaker implantation 51 . These results confirm the findings of a previous meta-analysis including 5,000 high-risk patients in which sutureless valve–AVR produced a reduction in early mortality and postoperative paravalvular leak 52 and echo the data from Biancari et al . in intermediate-risk patients 53 .…”
Section: Transcatheter Aortic Valve Replacements: Results and Comparisupporting
confidence: 91%
“…However, when a comparison with conventional AVR was made, outcomes were burdened by similar mortality but a reduced rate of permanent pacemaker implantation 51 . These results confirm the findings of a previous meta-analysis including 5,000 high-risk patients in which sutureless valve–AVR produced a reduction in early mortality and postoperative paravalvular leak 52 and echo the data from Biancari et al . in intermediate-risk patients 53 .…”
Section: Transcatheter Aortic Valve Replacements: Results and Comparisupporting
confidence: 91%
“…Other groups have used sutureless aortic valves in high-risk patients suffering from multiple-valve disease, with excellent results [ 22 ]. Takagi et al [ 23 ], in a recent meta-analysis of comparative studies between sutureless valves and TAVI, demonstrated a statistically significant reduction in early mortality in favor of sutureless valves over TAVI (2.5% vs. 7.3%; OR, 0.33 95% CI, 0.16–0.69; p=0.003) and a significant reduction of paravalvular leakage (3.5% vs. 33.2%; OR, 0.09; 95% CI, 0.05–0.16; p<0.00001), which has a significant influence on late mortality, as previously described. Furthermore, the economic impact of TAVI on society should not be underestimated, which clearly favor sutureless aortic valves [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these valve types facilitate minimally invasive AVR, which was limited in the past due to extended procedural times. Consecutively, several reports and meta-analyses compared AVR using sutureless and rapid-deployment aortic valves to TAVI [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The results led to the common conclusion supporting the use of SURD-AVR as an alternative to TAVI in high- or intermediate-risk patients requiring aortic valve replacement.…”
Section: Introductionmentioning
confidence: 99%